FAKTOR RISIKO HEMORRHAGE PASCA POST PARTUM - Ul-Ilmi, Annisa; Reka Lagora Marsofely, Serilaila, (JURNAL MEDIA KESEHATAN, 2018)
Bleeding is one of the causes of maternal deaths at Curup General Hospital in 2016with the number of cases as many as 123 cases. Many factors affect the occurrence of postpartumbleeding such as parity, birth spacing, age and anemia. This study aims to determine the riskfactors that affect post partum hemorrhage at Curup General Hospital District Rejang LebongYear 2016. Descriptive analytic research method with case control design. The sample was 246with ratio 1 between case group and control group (123). Data were analyzed by univariate,bivariate and multivariate using cgi square test and binary logistic regression. There was nocorrelation between birth and postpartum hemorrhage (p-value = 0.199, OR = 1.392), there was acorrelation between birth age and postpartum hemorrhage (p-value = 0.002, OR = 2.220) and noanemia relationship with postpartum hemorrhage (p-value = 0.294, OR = 0.759). The mostinfluential factors for post partum bleeding were parity (p-value = 0.044, OR = 0.589). Especiallyin mothers to be delivered in specific and comprehensive detection especially for mother primi orgrandemultipara especially at the time of III and IV by doing active management action of thirdstage so as to prevent the occurrence of uterine atony.